ChemInform Abstract: Facile Synthesis of 3‐Aryloxindoles via Broensted Acid Catalyzed Friedel—Crafts Alkylation of Electron‐Rich Arenes with 3‐Diazooxindoles. Issue 48 (2nd December 2014) - Zhai, Changwei; Xing, Dong; Jing, Changcheng; Zhou, Jun; Wang, Chengjin; Wang, Dongwei; Hu, Wenhao
Abstract The 3‐Aryloxindoles are obtained with high regioselectivities under mild and metal‐free reaction conditions.